Always available? A systematic review on extended work-related availability, health outcomes and work-family conflict - Renk, Simon; Sutter, Christine (Frontiers in Psychology, 2026)
IntroductionThis study critically explores the link between work-related extended availability, work-family conflict, and health outcomes through a systematic literature review, incorporating various theoretical frameworks, including the Work-Life Border Theory, the Job Demands-Resources Model, and the Conservation of Resources Theory.MethodsFollowing PRISMA 2020 guidelines, 17 studies were selected for the final analysis.ResultsThe review shows that higher levels of work-related extended availability are associated with increased work-family conflict and poorer health outcomes, notably higher stress, burnout, and reduced mental well-being. The research identifies key moderating factors such as organizational conditions (like structural autonomy and workload control) and boundary management style, which can lessen or intensify the negative impacts of work-related extended availability.DiscussionThese results deepen the understanding of the complex, conditional relationship between work-related extended availability and work-family conflict, highlighting the need for nuanced, context-aware strategies that address individual differences and organizational settings. This work provides valuable theoretical insights and practical guidance for managing the challenges of work-related extended availability in modern organizations. For future studies, examining additional moderation effects is recommended, employing longitudinal designs, and broadening the research scope to include high-risk professions.